2020
DOI: 10.1101/2020.04.27.063727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput organoid screening enables engineering of intestinal epithelial composition

Abstract: Barrier tissue epithelia play an essential role in maintaining organismal homeostasis, and changes in their cellular composition have been observed in multiple human diseases.Within the small intestinal epithelium, adult stem cells integrate diverse signals to regulate regeneration and differentiation, thereby establishing overall cellularity. Accordingly, directing stem cell differentiation could provide a tractable approach to alter the abundance or quality of specialized cells of the small intestinal epithe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…However, the requirement of porous culture inserts limits the application of ALI culture to smaller-scale experiments. In contrast, nasal organoids bring the possibility to perform high-throughput screening ( Phan et al, 2019 ; Mead et al, 2020 preprint). Furthermore, evaluation of the expression levels of the mesenchymal stem cell markers CD73, CD90, CD105 and the hematopoietic stem cell marker CD45 in HNECs (monolayers) showed that the quality of the cells was maintained up to passage four ( Muhammed et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the requirement of porous culture inserts limits the application of ALI culture to smaller-scale experiments. In contrast, nasal organoids bring the possibility to perform high-throughput screening ( Phan et al, 2019 ; Mead et al, 2020 preprint). Furthermore, evaluation of the expression levels of the mesenchymal stem cell markers CD73, CD90, CD105 and the hematopoietic stem cell marker CD45 in HNECs (monolayers) showed that the quality of the cells was maintained up to passage four ( Muhammed et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%